RETRACTED: A Matrine Derivative M54 Suppresses Osteoclastogenesis and Prevents Ovariectomy-Induced Bone Loss by Targeting Ribosomal Protein S5 - Xin, Zhi; Jin, Cui; Chao, Liu; Zheng, Zhang; Liehu, Cao; Panpan, Pan; Weizong, Weng; Xiao, Zhai; Qingjie, Zhao; Honggang, Hu; Longjuan, Qin; Xiao, Chen; et al. (Frontiers in Pharmacology, 2018)
Postmenopausal osteoporosis (PMOP) is a metabolic bone disorder characterized by low bone mass and micro-architectural deterioration of bone tissue. The over-activated osteoclastogenesis, which plays an important role in osteoporosis, has become an important therapeutic target. M54 was a bioactive derivative of the Chinese traditional herb Matrine. We found that M54 could suppress RANKL-induced osteoclastogenesis in bone marrow mononuclear cells (BMMCs) and RAW264.7 cells through suppressing NF-κB, PI3K/AKT, and MAPKs pathways activity in vitro, and prevent ovariectomy-induced bone loss in vivo. Our previous study has proved that ribosomal protein S5 (RPS5) was a direct target of M19, based on which M54 was synthesized. Thus we deduced that M54 also targeted RPS5. During osteoclastogensis, the RPS5 level in RAW264.7 cells was significantly down-regulated while M54 could maintain its level. After RPS5 was silenced, the inhibitory effects of M54 on osteoclastogenesis were partially compromised, indicating that M54 took effects through targeting RPS5. In summary, M54 was a potential clinical medicine for post-menopause osteoporosis treatment, and RPS5 is a possible key protein in PMOP.